(sinx^{2} theta)\frac{x}{y}(1+costheata)" alt="(sinx^{2} theta)\frac{x}{y}(1+costheata)" align="absmiddle" class="latex-formula">
1 answer:
The result of expanding the trigonometry expression
is ![cos^0(\theta) + \cos(\theta) - \cos^2(\theta) - \cos^3(\theta)](https://tex.z-dn.net/?f=cos%5E0%28%5Ctheta%29%20%2B%20%5Ccos%28%5Ctheta%29%20-%20%5Ccos%5E2%28%5Ctheta%29%20-%20%5Ccos%5E3%28%5Ctheta%29)
<h3>How to evaluate the expression?</h3>
The expression is given as:
![\sin^2(\theta) * (1 + \cos(\theta))](https://tex.z-dn.net/?f=%5Csin%5E2%28%5Ctheta%29%20%2A%20%281%20%2B%20%5Ccos%28%5Ctheta%29%29)
Express
as
.
So, we have:
![\sin^2(\theta) * (1 + \cos(\theta)) = (1- \cos^2(\theta)) * (1 + \cos(\theta))](https://tex.z-dn.net/?f=%5Csin%5E2%28%5Ctheta%29%20%2A%20%281%20%2B%20%5Ccos%28%5Ctheta%29%29%20%3D%20%20%281-%20%5Ccos%5E2%28%5Ctheta%29%29%20%2A%20%281%20%2B%20%5Ccos%28%5Ctheta%29%29)
Open the bracket
![\sin^2(\theta) * (1 + \cos(\theta)) = 1 + \cos(\theta) - \cos^2(\theta) - \cos^3(\theta)](https://tex.z-dn.net/?f=%5Csin%5E2%28%5Ctheta%29%20%2A%20%281%20%2B%20%5Ccos%28%5Ctheta%29%29%20%3D%20%201%20%2B%20%5Ccos%28%5Ctheta%29%20-%20%5Ccos%5E2%28%5Ctheta%29%20-%20%5Ccos%5E3%28%5Ctheta%29)
Express 1 as cos°(Ф)
![\sin^2(\theta) * (1 + \cos(\theta)) = cos^0(\theta) + \cos(\theta) - \cos^2(\theta) - \cos^3(\theta)](https://tex.z-dn.net/?f=%5Csin%5E2%28%5Ctheta%29%20%2A%20%281%20%2B%20%5Ccos%28%5Ctheta%29%29%20%3D%20%20cos%5E0%28%5Ctheta%29%20%2B%20%5Ccos%28%5Ctheta%29%20-%20%5Ccos%5E2%28%5Ctheta%29%20-%20%5Ccos%5E3%28%5Ctheta%29)
Hence, the result of expanding the trigonometry expression
is ![cos^0(\theta) + \cos(\theta) - \cos^2(\theta) - \cos^3(\theta)](https://tex.z-dn.net/?f=cos%5E0%28%5Ctheta%29%20%2B%20%5Ccos%28%5Ctheta%29%20-%20%5Ccos%5E2%28%5Ctheta%29%20-%20%5Ccos%5E3%28%5Ctheta%29)
Read more about trigonometry expressions at:
brainly.com/question/8120556
#SPJ1
You might be interested in
Answer:
36 minutes is the answer!
Step-by-step explanation:
Answer:
The age of the youngest friend is 9 years old.
Step-by-step explanation:
3a = 30 - 3
= 27 ÷ 3
= 9
= 9 + 10 + 11 = 30
= 9 is the smallest number. So, the youngest friend is 9 years old.
![\frac{a}{7} + \frac{5}{7} = \frac{2}{7} \\ \frac{a + 5}{7} = \frac{2}{7} \\ 7(\frac{a + 5}{7}) = 7(\frac{2}{7})](https://tex.z-dn.net/?f=%5Cfrac%7Ba%7D%7B7%7D%20%2B%20%5Cfrac%7B5%7D%7B7%7D%20%3D%20%5Cfrac%7B2%7D%7B7%7D%20%5C%5C%20%5Cfrac%7Ba%20%2B%205%7D%7B7%7D%20%3D%20%5Cfrac%7B2%7D%7B7%7D%20%5C%5C%207%28%5Cfrac%7Ba%20%2B%205%7D%7B7%7D%29%20%3D%207%28%5Cfrac%7B2%7D%7B7%7D%29)
a + 5 = 2
a + 5 - 5 = 2 - 5
a = -3
Hope this helps! :)
Answer:
1/5
Step-by-step explanation:
Gradient is another word for slope. To find the gradient, we have to use a formula.
The correct answer it would be B
Ford